ТО A QUESTION OF OWN STYLE OF PROFESSIONAL WORK OF THE FUTURE MUSICIAN-TEACHER (Pedagogy of Higher and Secondary Education, 2007)
In the article is reveals a new conceptual approach to realization of professional training of musician-educational specialist which is shown in making and the next forming of personal style of his professional activity.
Keywords: personal style; professional activity; musician-educational specialist